Bridging production factors allocation and environmental performance of China's heavy-polluting energy firms: The moderation effect of financing and internationalization. (1st May 2021) - Liu, Tiansen; Song, Yazhi; Xing, Xinpeng; Zhu, Yue; Qu, Zhengyu
Abstract: This study extends our understanding of the production factors allocation and environmental performance relationship by considering the moderation effect of financing and internationalization with China's heavy-polluting energy firms as sample due to their significant impact on climate change, substantial contribution to boom of industrial sectors, and distinctive governance structures. We focus on five types of production factors, i.e. capital (asset-liability ratio), labor (production-typed staff size), technology (R&D intensity), information (inventory size), and institution (state-holding size) factors. Our analysis indicates that lower asset-liability ratio, lower R&D intensity, lower inventory, and higher state-holding significantly enhance environmental performance, while the degree of internationalization has a significantly negative influence on environmental performance. It can be also concluded that financing (as a capital "introduction" strategy) and internationalization (as a market "going-global" strategy) can enhance the effect of slack production factors on environmental performance, i.e. reducing the waste of slack resources. Heterogeneity test shows that higher degrees of financing and internationalization more significantly enhance the contribution of slack production factors to environmental performance than that of lower degrees. Our findings have key implications, particularly for heavy-polluting energy firms of emerging markets, in reasonably deploying production factors to achieve environmental improvement by attracting financing and global markets. Highlights: A tense production factors allocation (PFA) enhances environmental performance (EP). Financing and internationalization enhance the contribution of slack PFA to EP. Higher levels of financing and internationalization have stronger moderation effects. It should improve the effect of PFA on EP by approaching financing and global market.